Adjusting Effects of Baicalin for Nuclear Factor-κB and Tumor Necrosis Factor-α on Rats With Caerulein-Induced Acute Pancreatitis - Dongbo Xue; Weihui Zhang; Yingmei Zhang; Haiyang Wang; Biao Zheng; Xingye Shi (Mediators of Inflammation)
Forty Wistar rats were divided into 5 groups, including the control group, the acute pancreatitis group (AP group, induced by intraperitoneal injections of caerulein), and the AP group treated with baicalin, the AP group treated with LPS, and the AP group treated with LPS and baicalin. Pathological damage of pancreatic tissue was scored with hematoxylin and eosin (HE) staining. The mRNA expression of TNF-α was measured with semiquantitative RT-PCR, and activation of NF-κB was detected with flow cytometry assay. It was shown in the results that the expression of TNF-α mRNA, activation of NF-κB, and pathological score of AP group were all obviously higher than those of control group (P<.01). In AP group treated with LPS, further rise of these values were observed (P<.01). In the AP group treated with baicalin, activation of NF-κB decreased (P<.05), and expression of TNF-α mRNA also obviously decreased (P<.01), while pancreatic pathological damage was alleviated at the same time (P<.01); similar results were observed in AP group treated with LPS and baicalin (P<.01), which indicated that baicalin might be applied to inhibit NF-κB activating and TNF-α expressing so as to treat AP.